The Ends of Lecirelin on the Destruction of Ovarian Cancer Cells - Tahoori, Fatemeh; Salehi-Najafabadi, Zahra (International Pharmacy Acta, 2024)
As a gynecological cancer, ovarian cancer has the highest lethality among females on the globe. Evidence shows that the GnRH agonists and antagonists dramatically inhibit the growth of most cancer cell lines expressing the GnRH receptor. The current research focuses on the effectiveness of three novel GnRH analogs showing anticancer activities on the cell lines of ovarian cancer. The present investigation synthesized Lecirelin in the solid phase and changed the peptide chain’s C-terminal. Two ovarian cancer cell lines were examined for the impacts of the purified peptides. The hydrazide derivative with an approximate concentration of 30 mg/mL (lC50 30) can kill more than half of the ovarian cancer cells, while the Lecirline needs twice more active ingredient to kill this amount of the cells (lC50 47, p = 0.001). Lecirelin and its hydrazide derivative have anticancer activity against ovarian cancer cells, and this GnRH analog may be considered a promising candidate for further studies.